THEME AND THEMATIC PROGRESSION OF UNDERGRADUATE THESES - Mubarak, Hamdan Zainu (IPI Garut Press, 2021)
This research aimed to analyze the theme and the thematic progression in undergraduate students’ theses. To achieve these aims, qualitative research embracing case study was chosen. The participants of this research were six undergraduate students from academic year 2016, 2017, and 2018 in one of colleges in Garut. The data, students’ theses, were collected by techniques of document study based on these themes (developing writing skill). The theory of theme by Butt et al (2000) and thematic progression by Bloor and Bloor (2004) was used to analyze the data. The result revealed that undergraduate students mostly used unmarked topical theme and reiteration pattern. It meant that the undergraduate students had tried to persuade the readers to accept their point of view and they had tried to make their text focus by repeating the same element as a theme